If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -4) = -6 Reorder the terms: 2(-4 + x) = -6 (-4 * 2 + x * 2) = -6 (-8 + 2x) = -6 Solving -8 + 2x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 2x = -6 + 8 Combine like terms: -8 + 8 = 0 0 + 2x = -6 + 8 2x = -6 + 8 Combine like terms: -6 + 8 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| 0.04x+0.07(13000-x)=780 | | -2x=4-x | | 9+6x-9=2+(-1)x-9 | | y=6y+5x | | 10x^2=-15x | | x-7=-7 | | 7z+1=62 | | -10=3y+11 | | 2x-5=-15 | | -141=-6x-6x+3 | | (3+2x)3=2+(-1)x | | (13-x)=780.00 | | 7x-5x=-20 | | 5=x-4 | | 5x-8-6x=-9 | | 3=y+5 | | 12x=11x-5 | | 2(x+4)=3(1+x) | | 2x-2+1x+5=180 | | h^2+3h-22=0 | | -8=4x+2x+4 | | -12y+8=-4 | | 5+0.50=1.00x | | 5x+4x+6+10x+12x-12=180 | | -6-4x+6x=-10 | | 7x-3x=44 | | 27+73= | | -2.9x=-52.2 | | 3(2x+4)=5(x-3) | | 3(X)-5=75 | | -3x+3y=-12 | | 2x^3+54=4x^2+x-1 |